Jak opisać dawne galicyjskie przedmieścia we współczesnym języku chińskim? Kognitywna analiza przekładów Sklepów cynamonowych Brunona Schulza - Jakubów, Zofia (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article is an analysis of the description of the garden in Bruno Schulz’s The Cinnamon Shops (Sklepy cynamonowe) and its two translations into Chinese. Wei-Yun Lin-Górecka has translated Schulz’s prose from the original Polish, while Lu Yuan’s translation is primarily based on English versions of his work. The analysis employs methods drawn from cognitive poetics and some elements of cognitive theory of translation, especially Elżbieta Tabakowska’s ideas on imagery and translation equivalence. The study helped characterize a complex conceptual blend found in the description and trace structural changes caused by the translators’ specific decisions. The translations are characterized by a relatively high level of equivalence. The conceptual blends they comprise differ from the one created by Bruno Schulz mostly in terms of the described elements’ positions on the empathy scale, which are mainly dependent upon the translators’ manner of using the devices of animation and anthropomorphism.